178 Paramedics' experiences attending and managing patients who fall. (20th November 2022) - Watkins, Paige; Buzzacott, Peter; Tohira, Hideo; Brink, Deon; Finn, Judith; Hill, Anne-Marie
Abstract : Background: A growing, and ageing, population is requiring an increasing number of ambulance attendances for falls in Western Australia (WA). However, there is limited understanding about the experiences of paramedics attending and managing these patients. Methods: A phenomenological study explored the experiences of a purposive sample of paramedics in WA. Semi-structured interviews were undertaken and thematically analysed, using an inductive approach. Results: Fourteen paramedics were interviewed (female = 5, rural experience = 4). Paramedics considered their role across a broad spectrum, ranging from 'emergency care' to 'holistic health care'. Participants experienced frustration attending patient falls in residential aged care facilities, as they reported that patient perspectives and paramedics' decisions were often not considered or over-ridden by policies. Availability of resources in the prehospital setting impacted practice and decision making and raised safety concerns regarding manual handling options. Attending patients who had repeated falls often resulted in frustration over a lack of alternative pathways, other than transport to hospital, that could be recommended. Participants' decisions regarding transport were influenced by managing risk and confidence in the employing ambulance service supporting their clinical decisions. Conclusion: Paramedics attending and managing adult patients who fell, suggested decisions regarding transport were influenced by a broad range of factors. Access to referral pathways for non-emergency home health care was viewed as a gap that should be addressed. Learning Outcomes: Paramedics suggest that alternative referral pathways for patient falls are required in the prehospital setting.